Timeliness of Financial Reporting and Its Impact on the Indian Capital Market: A Theoretical and Empirical Exploration - Bhatia, Amit (Digital Repository of Theses - SSBM Geneva, 2025)
This study examines the timeliness of financial reporting and its effects on the Indian capital market, emphasizing its importance in promoting transparency, decreasing information asymmetry, and bolstering investor confidence. Based on agency and signaling theories, the research employs a mixed-methods approach that integrates quantitative analysis of reporting timelines from large-, mid-, and small-cap companies with qualitative data drawn from stakeholder interviews. The findings indicate that large-cap companies provide their reports more swiftly due to superior governance and resources, whereas mid- and small-cap companies experience delays attributed to resource limitations, manual operations, and outdated technology. ANOVA and regression analyses demonstrate that the size of a firm and agency-related governance practices have a substantial impact on timeliness, while the applicability of signaling theory is limited across many sectors. Qualitative insights pinpoint major reasons for reporting delays, including fragmented regulatory requirements, lack of ERP integration, insufficient board oversight, and skill shortages in finance teams. The study underscores the penalty-oriented nature of India’s compliance landscape and advocates for a transition to incentive-driven transparency. By referencing best practices from companies like Infosys and HDFC Bank, the research suggests actionable reforms such as enhancing the capabilities of audit committees, streamlining compliance procedures, and utilizing digital technologies. The study provides valuable insights for regulators, corporate leaders, auditors, and investors, stressing that timely financial reporting is essential for effective market operations and corporate governance. It also sets the stage for future research examining sectoral variations, technological advancements, and global comparisons in reporting practices.